Persistence of mule deer pellet groups on Chihuhuan Desert - Esparza-Carlos, Juan Pablo (THERYA, 2024)
The persistence of fecal or pellet groups is indispensable when using the pellet group counting technique to estimate population densities and relative abundances of deer, as well as other herbivores. This technique is widely employed worldwide, and in México, the majority of deer abundance estimates have been made using this tool. However, for mule deer (Odocoileus hemonious) in México, there is no data on the persistence of pellet groups, and there is only one study on white-tailed deer. The pellet group counting technique has two main methods: a) "Fecal Standing Crop," where the accumulated pellet groups in plots are counted in a single visit, and b) "Fecal Accumulation Rate," which estimates density based on the accumulation of new fecal groups between two sampling periods, initially requiring the removal of all fecal groups from plots and counting again after some time. Both methods require knowing the pellet group disappearance rate during the pellet group accumulation period. This information is fundamental to understanding the ecology and making precise decisions in the management and conservation of mammals, such as mule deer, a species that is declining in some regions of México. Due to the lack of studies on the persistence of pellet group of mule deer in México, the aim of this study was to determine the persistence of mule deer fecal groups and their color changes over time, to establish pellet accumulation periods for estimating population abundances without biases when using this technique in arid habitats. We monitored 102 fecal groups for four years in the Chihuahuan Desert, finding that pellet groups are only lost during the summer rainy season. All pellet groups deposited between October and May were present, and all pellet groups turned white only after the first summer rainy season. The persistence of pellet groups was similar across seasons (fall, winter, spring) and deposition years (2004 to 2006). Some pellet groups persisted for over four years. The data suggest that the only source of degradation of pellet groups is summer rains, and no degradation by biological agents, such as fungi or insects, was observed. In summary, in arid areas, to estimate deer use or density throughout the entire dry season through pellet group counting, it is suggested that only two visits with either of the mentioned techniques are needed. If "Fecal Standing Crop" is used, there is now certainty that all non-white pellets are post the summer rainy season. If the "Fecal Accumulation Rate" technique is used, there is certainty that there will be no loss of pellets groups between the accumulation period of the entire dry season, approximately 7.5 months later. By reducing the number of visits, it allows us to cover more sampling sites, expand the study area, and obtain more precise estimates that will help understand ecological aspects and make management decisions.